The Efficacy of Parent-Child Interaction Therapy (PCIT) in Children with Attention Problems, Hyperactivity, and Impulsivity in Dubai - Saad A. Al Sehli; Maya Helou; Meshal A. Sultan (Case Reports in Psychiatry)
Disruptive behaviors can be associated with significant functional impairment. Early intervention for young children is essential to prevent long-term consequences. Parent-Child Interaction Therapy (PCIT) is a psychotherapeutic intervention, which has shown to be effective for children with externalizing symptoms. We present the treatment course of PCIT for two kindergarten children. The first has Attention-Deficit/Hyperactivity Disorder (ADHD), and the second has frontal lobe epilepsy. Both presented with attention problems, hyperactivity, and impulsivity associated with significant impairment in multiple settings. Two certified PCIT therapists provided 17 sessions to the parents of the first patient and 25 sessions to the parents of the second patient. Most of the sessions were in-person; however, some were “virtual” due to the circumstances associated with the COVID-19 pandemic. Parents of both patients achieved the “mastery” criteria. In both cases, PCIT contributed to improving the disruptive behaviors. PCIT may serve as an effective therapeutic option for young children with externalizing symptoms in Dubai.